LATAR BELAKANG TEOLOGIS, FILOSOFIS, SOSIOLOGIS DAN POLITIS, LAHIRNYA INTEGRASI AGAMA DAN SAINS SERTA MASA DEPANNYA - Ferizal Rachmad; Amril (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The purpose of this article is to find out how the theological, philosophical, sociological and political backgrounds of the birth of the integration of the sciences of religion and science, and its future. This writing uses the method of literature review. Literature review contains reviews, summaries, and written thoughts about several sources of literature (can be in the form of articles, books, slides, information, the internet, etc.), about the topics discussed. The results of the research show that the birth of the integration of religion and science has a background that can be analyzed from various aspects starting from theological, philosophical, sociological and political aspects. The future of the integration of religion and science depends on the seriousness of all stakeholders in the world of Islamic education in implementing all the approaches to the integration of religion and science. In line with that,Indonesian Muslim thinkers have designed a conception of scientific integration with an emphasis on the epistemological aspect, in addition to the ontological aspect,the following are their conceptions of thought which are grouped based on the common thread of the main ideas, namely: (a) Integrative-Interconnective Approach Model (Net Profit), (b) Islamic Objectification Model, and (c) Holistic Integration Model.